The Self-Regulated Learning Strategies in Vocabulary Learning Using Socrative App - Regina Octaviani; Sri Setyarini Setyarini; Rojab Siti Rodliyah (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2023)
Self-Regulated Learning (SRL) strategies has been implemented in psychological learning context. The research regarding the SRL has dynamically spread to some recent issues in the learning process, including the language learning and technology to obtain students’ learning achievement. Therefore, this study hisghlights the English language learning among secondary school students regarding the vocabulary learning achievement through one of the Mobile Apps called Socrative. This study employed a qualitative research to investigate the issue and involved 21 students as participants who were observed and interviewed. The findings figured out that the students implemented two out of fourteen SRL strategies in the EFL vocabulary learning; (1) Seeking assistance and (2) Organization, but the fact revealed that the students did not make an outstanding result based on their work on Socrative regarding to the vocabulary learning.